(untitled) (Training and Practice : Journal of Educational Sciences, 2025)
Our research focuses on university students, mentors of the Let’s Teach for Hungary (TM) national mentoring program. The analysis categorizes the mentoring practices in the TM program. In this research, we inquire the perceptions of mentors about the roles of their supervising teachers, their relationships with them, and possible development of the supervising courses. The paper is based on complex research: we rely on a questionnaire format data collection (N = 180, N = 50), which we interpret via qualitative strategy using interview format research (N = 25). The results highlight that mentors do not turn to their supervising teachers in all instances, but their importance is stressed, ad many perceive them as a “safety net”. The relationships with the supervising teacher inform us about that the roles of supervising teachers exceed professional help and integrate emotional support of mentors. The novelty of this paper is that as to the best of our knowledge, this research is the first attempting the analysis of the supervision in this program. The results indicate that the support of mentors is essential in this, and other mentoring programs.